Asymmetric patch element reflectarray with dual linear and dual circular polarization - Shamsan, Zaid Ahmed; Dahri, Muhammad Hashim; Jamaluddin, Mohd Haizal; Abbasi, Muhammad Inam; Kamarudin‬, ‪Muhammad Ramlee; Che Seman, ‪Fauziahanim; Ashyap, Adel Yahya Isa; AlMuhanna, Khalid; Alorifi, Fawzi (Tech Science Press, 2022)
A reflectarray antenna consisting of asymmetrical patch elements is proposed, which is capable of producing dual linear and dual circular polarized operation at 26 GHz frequency. The main purpose of this design is to support four different polarizations using the same patch element. The proposed reflectarray has a single layer configuration with a linearly polarized feed and circular ring slots in the ground plane. Asymmetric patch element is designed from a square patch element by tilting its one vertical side to some optimized inclination. A wide reflection phase range of 600° is obtained with the asymmetric patch element during unit cell measurements. A 332 element circular aperture reflectarray is designed with the proposed configuration and experimentally validated with a linearly polarized prime feed configuration. Two different orientations of mirror and non-mirror asymmetric patch elements on the surface of reflectarray are analyzed. Dual linear polarization is obtained with the mirror orientation of the asymmetric patch elements on the surface of reflectarray. Alternatively, asymmetric patch elements without mirror orientation are demonstrated to produce dual circular polarization with the same linearly polarized feed. A maximum measured gain of 24.4 dB and 26.1 dB is achieved for dual linear and dual circular polarization, respectively. Their respective measured efficiencies are 28% and 41.3%, which are supported by a maximum −3 dB gain bandwidth of 13.8% and 11.5%. The circular polarization operation of the reflectarray is also supported by a 6 dB axial ratio bandwidth of 9.2%. The proposed asymmetric patch reflectarray antenna with polarization diversity, wide bandwidth and high gain is suitable to be used in many high frequency applications of 5G communication.